CGIAR Open and FAIR Data Assets Policy - CGIAR Platform for Big Data in Agriculture (2021)
The CGIAR Open and Fair Data Assets Policy clarifies expectations regarding the management and dissemination of data assets to ensure they are as open as possible, FAIR, and managed responsibly.